Resposta da canola a fontes, doeses e parcelamento de nitrogênio, em Toledo PR - Kaefer, João Edson (2012)
The canola term is an acronym for Canadian Oil Low Acid and was adopted as the standard to indicate low levels of erucic acid and glucosinolates. In general, tropical soils are poor in available nitrogen (N) because of the low stocks of organic matter, requiring the external supply of N to meet the demands of the culture. Among the main sources of N used in the culture of canola are nitrogen fertilizers urea and ammonium sulfate. Besides the choice of fertilizer nitrogen source related to N, to adjust the timing of nitrogen application at the time of greatest demand increased demand will increase crop production efficiency In view of this, six experiments were carried out from May 2009 to April 2010. These experiments were mainly aimed at evaluating the response of canola to nitrogen sources and application methods (seeding and / or coverage) of nitrogen fertilizer. All experiments were conducted in the experimental units at the Catholic University of Paraná - PUCPR - Toledo campus. To attend the responses of canola relative to rates and N sources were implanted three experiments in randomized blocks in a 7x2 factorial arrangement, consisting of seven levels of nitrogen at sowing (0, 20, 40, 60, 80, 100 and 120 kg ha -1) and two N sources (ammonium sulphate and urea), with four replications. To attend the responses of canola on the forms of nitrogen application and nitrogen sources were implanted over three experiments, which are conducted in randomized blocks in a 5x2 factorial arrangement consisting of five forms of nitrogen in the seeding and / or in coverage, respectively (0 and 0, 120 and 0, 0 and 120, 40 and 80, 80 and 40 kg N ha-1) and two nitrogen sources (ammonium sulphate and urea), with four replications. The coverage fertilization was performed in stage B4. The six experiments were carried out in three production cycles, two experiments in each cycle, corresponding to the following sowing dates: cycle 1: 12/05/2009; cycle 2: 20/06/2009 and cycle 3: 23/04 / 2010. All treatments received a fertilizer equivalent to 300 kg ha-1 00-25-25 formulation, each plot received the amount of nitrogen corresponding to the predetermined treatment. For the six experiments were evaluated the basal diameter, plant height, number of plants m-2, dry leaves, dry weight of stem + petioles, inflorescence dry mass, total plant dry mass, leaf area, area ratio of leaf, mass of pods per plant, weight per pod, weight of grains per pod, thousand grain weight, yield, leaf N content, protein and oil content in grain and oil yield per hectare. The results show that the variables were not influenced by sources of nitrogen fertilizer, ammonium sulfate and urea, for any of the six experiments conducted. The response to N rates influence these variables measured, and the higher productivity achieved with 88 kg ha-1 N. The increase of N doses promotes an increase in the protein reducing therefore the oil content in grains. The forms of nitrogen application also influenced the variables measured, and the best results achieved by the split of applying fertilizer at planting one-third and two-thirds coverage (40 and 80 kg N ha-1)